Demystifying Drugs - Goldberg, Ted. author. aut Link
VII, 291 p.
Keywords: Based on extensive participant observation research, a life-history model is presented to explain why very few of those who come into contact with narcotics become problematic consumers; that is make drugs one of the most central elements in their lives. The model covers four stages in the deviant career; two preceding and two subsequent to the individual's narcotics debut. Prohibition and harm reduction as models for intervention are presented, and the implications for drug policy of the life-history model are discussed.